The Representation of Facts about Old Russian Charters on the Semantic Web: Attempto Controlled English (ACE) - Ivanovs, Aleksandrs; Varfolomeyev, Aleksey (Slavistica Vilnensis, 2019)
This paper discusses some promising approaches to the representation of meta-information (facts) about medieval Russian charters on the Semantic Web in order to provide researchers with appropriate tools for the capture, aggregation, and semantic linkage of facts related to the charters and automatic logical inference. The authors demonstrate the actual and potential possibilities of a controlled natural language, ACE (Attempto Controlled English), in the representation of the meta-information about Old Russian charters. Recent research conducted by the authors confirms that the prospects for using ACE as a tool for representation of the facts about the charters on the Semantic Web are closely connected with the possibilities to make logic inferences based on ACE texts. Therefore, special attention is devoted to ACE tools, especially to Ace Rules and ACE Reasoner (RACE).